Further Results on Meromorphic Functions and Their $n$th Order Exact Differences with Three Shared Values (Communications in Mathematical Research, 2019)
Let $E(a,\,f)$ be the set of $a$-points of a meromorphic function $f(z)$ counting multiplicities. We prove that if a transcendental meromorphic function $f(z)$ of hyper order strictly less than 1 and its $n$th exact difference $Δ_c^nf(z)$ satisfy $E(1,\,f)=E(1,\,Δ_c^nf)$, $E(0,\,f)\subset E(0,\,Δ_c^nf)$ and $E(∞,\,f)\supset E(∞,\,Δ_c^nf)$, then $Δ_c^nf(z)\equiv f(z)$. This result improves a more recent theorem due to Gao et al. (Gao Z, Kornonen R, Zhang J, Zhang Y. Uniqueness of meromorphic functions sharing values with their $n$th order exact differences. Analysis Math., 2018, https://doi.org/10.1007/s10476018-0605-2) by using a simple method.
Keywords: meromorphic function; exact difference; uniqueness; shared value